1968
DOI: 10.1152/ajplegacy.1968.215.2.429
|View full text |Cite
|
Sign up to set email alerts
|

Urea concentrations in tubular fluid and in renal tissue of nondiuretic rats

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1972
1972
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…5) and Pu = 39 X 1O-' cm/s (Table I, IMCDA), and 6C = 70 mM, the calculated rate of urea absorption from the inner medullary collecting ducts is 1.4 X 10-3 mmol/min. If this value is compared with the filtered load of urea in normal rats (6 X 10-3 mmol/min [38]), the predicted urea absorption from the inner medullary collecting ducts will be 1.4/6 X 100% = 23% of the filtered load. This value is consistent with the range observed (15-30%) in micropuncture and microcatherization studies (12 1 3), in-ofurea out ofthe pelvic space.…”
Section: Resultsmentioning
confidence: 99%
“…5) and Pu = 39 X 1O-' cm/s (Table I, IMCDA), and 6C = 70 mM, the calculated rate of urea absorption from the inner medullary collecting ducts is 1.4 X 10-3 mmol/min. If this value is compared with the filtered load of urea in normal rats (6 X 10-3 mmol/min [38]), the predicted urea absorption from the inner medullary collecting ducts will be 1.4/6 X 100% = 23% of the filtered load. This value is consistent with the range observed (15-30%) in micropuncture and microcatherization studies (12 1 3), in-ofurea out ofthe pelvic space.…”
Section: Resultsmentioning
confidence: 99%
“…If urea enters the loop then (TF/P) urea/(TF/P) inulin ratio would be higher in the early distal tubule than the late PCT. Conflicting data exist on this point in animals not undergoing saline diuresis (12,14,24); however, most of the observations suggest that recirculation of urea does exist, thus implying that either the descending or ascending thin limb of Henle should be relatively permeable to urea. In the present study, the role of the DLH was examined directly and noted to be as impermeable to urea as previously reported for Na (Table VII).…”
Section: Discussionmentioning
confidence: 99%
“…Micropuncture studies have previously demonstrated that proximal tubular-fluid-to-plasma-urea concentrations are greater than one (12,(14)(15)(16)(17) with most of the value ranging between 1.4 and 1.5. In the absence of active urea secretion this would imply that the PCT is relatively impermeable to urea and is consistent with the Curea of 0.91.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were anesthetized with sodium pentobarbital (35 mg/kg, i.v.) and prepared for micropuncture of the left kidney as described previously [11]. A carotid ar tery was catheterized for determination of blood pressure and for collection of arterial blood sam ples.…”
Section: Methodsmentioning
confidence: 99%